Padepokan Pencak Silat Bandrong Badak Putih dalam Pelestarian Kesenian Silat dan Debus di Kecamatan Citangkil, Kota Cilegon Tahun 2015-2023 - Inayah, Hania Nur; Anak Agung Ayu Rai Wahyuni; Anak Agung Ayu Dewi Girindra Wardani (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study examines the role of the Bandrong Badak Putih Pencak Silat Padepokan in the preservation of the traditional arts of Debus and Silat in Citangkil District, Cilegon City, in the period 2015 to 2023. The main focus of this research is to understand how this relatively young padepokan is able to maintain its existence and even develop rapidly in the midst of globalization, compared to several other padepokans that were established earlier. In the context of modernization which often encourages a shift in local cultural values, the existence and consistency of this padepokan is an interesting phenomenon to be further researched. The formulation of the problem in this study includes: (1) how the role of Padepokan Bandrong Badak Putih in the preservation of Debus and Silat arts; (2) why this padepokan is able to survive in the midst of the onslaught of modernization and globalization; and (3) what are the social and cultural implications of its existence on the surrounding community. This research aims to analyze the contribution of padepokan in preserving local cultural heritage, identify conservation strategies carried out, analyze supporting and inhibiting factors, and understand the socio- cultural impact of the existence of padepokan in the Citangkil community. The method used is qualitative descriptive with data collection techniques through in- depth interviews, field observations, and documentation studies. Data analysis was carried out thematically based on historical theory and cultural preservation theory. The results of the study show that Padepokan Bandrong Badak Putih plays an active role in training, cultural performances, and regeneration through youth involvement. The success of this padepokan is supported by the collective spirit, adaptation to technology, and instilled cultural values. The implications are not only on cultural preservation, but also on strengthening local identity and social solidarity of the community.